Phytochemical Study of Some Medicinal Plant - Sarraf, S.; Tyagi, S.; Ojha, A.C.; Rawat, G.S. (Asian Journal of Chemistry, 2010)
Leaves, root and bark of Adhatoda vasica nees, leaves, root and seed of Argemone mexicana Linn. and leaves and root of Asparagus racemosus Willd. were analysed for the estimation of sugar and vitamins. In genera' thirteen sugars were identified in various medicinal plant parts. A. vasica contains more amount of free sugars as compared to other plants.